2017
DOI: 10.1016/j.cois.2017.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Influence of heavy metal contamination on urban natural enemies and biological control

Abstract: Urban agriculture is increasing worldwide. A history of contamination within urban landscapes may negatively impact the biota necessary for sustainable crop production, including arthropod natural enemies. This investigation revealed that heavy metal contamination can influence the composition of natural enemy communities and exposure can have reproductive, developmental, immunological and behavioral impacts on predators and parasitoids. Natural enemies exposed to heavy metals typically live shorter lives, tak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 67 publications
1
11
0
1
Order By: Relevance
“…Legacies of heavy metal contamination in urban soils are a consequence of past industrial manufacturing, smelting, and waste disposal, as well as widespread use of products such as leaded gasoline and lead‐based paints (Pouyat et al 2010, Wortman and Lovell 2013). Exposure to elevated levels of heavy metal pollutants in urban soils can have reproductive (Hendrickx et al 2003, Lagisz and Laskowski 2008), developmental (Scheifler et al 2002, Lagisz 2008, Cheruiyot et al 2013), immunological (Stone et al 2002, Migula et al 2004, Sorvari et al 2007), and behavioral (Eraly et al 2009, Sorvari and Eeva 2010) impacts on arthropods, including ground‐dwelling predators that experience direct and indirect exposure (Gardiner and Harwood 2017). Contamination of vacant lot soils by heavy metals was identified as a local environmental stressor for ground‐dwelling beetle communities in this study, with more functionally similar beetle communities found in highly contaminated vacant lots.…”
Section: Discussionmentioning
confidence: 99%
“…Legacies of heavy metal contamination in urban soils are a consequence of past industrial manufacturing, smelting, and waste disposal, as well as widespread use of products such as leaded gasoline and lead‐based paints (Pouyat et al 2010, Wortman and Lovell 2013). Exposure to elevated levels of heavy metal pollutants in urban soils can have reproductive (Hendrickx et al 2003, Lagisz and Laskowski 2008), developmental (Scheifler et al 2002, Lagisz 2008, Cheruiyot et al 2013), immunological (Stone et al 2002, Migula et al 2004, Sorvari et al 2007), and behavioral (Eraly et al 2009, Sorvari and Eeva 2010) impacts on arthropods, including ground‐dwelling predators that experience direct and indirect exposure (Gardiner and Harwood 2017). Contamination of vacant lot soils by heavy metals was identified as a local environmental stressor for ground‐dwelling beetle communities in this study, with more functionally similar beetle communities found in highly contaminated vacant lots.…”
Section: Discussionmentioning
confidence: 99%
“…For example, increased evapotranspiration, such as in Madison, WI, USA [22], is influenced by soil moisture and urban warming, and may play a significant role in tree physiology [108][109][110], condition and herbivory [55,73]. Simultaneous measurement of climate variables and urban variables such as land cover, population density and impervious surface is crucial in addressing confounding factors associated with urban environments, such as air quality [65,66], water or soil pollution [111][112][113][114], soil compaction and invasive species [115][116][117]. Understanding the potential for acclimation or adaptive evolution by urban species (and the potential for non-adaptive genetic drift and gene flow) is also important in validating cities as surrogates for global change.…”
Section: (B) Validating Climate Variables and Evolutionary Potential mentioning
confidence: 99%
“…Work on different aspects of populational diversity on genetic (Siepel, 1988;Den Boer et al, 1992;Lagisz et al, 2010) and morphological (Emetz, 1986;Schwerk & Jaskuła, 2018) levels allow one to state that P. oblongopunctatus is one of the best studied species of ground beetles. P. oblongopunctatus is a typical element of urban forest plantations and anthropogenically transformed territories (Grechanichenko & Guseva, 2000;Magura et al, 2008;Gardiner & Harwood, 2017). Thus, the studied species of ground beetle is a practical object for modeling changes in the range in conditions of global climate changes, one of the priority factors which affects natural populations in XXI century (Kotze et al, 2011).…”
Section: Introductionmentioning
confidence: 99%